2019
DOI: 10.1002/app.47656
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired polydopamine coating‐assisted electrospun polyurethane‐graphene oxide nanofibers for bone tissue engineering application

Abstract: It is inevitable to replace the tissues and organs that have been malfunctioning due to trauma or difference diseases, so tissue engineering can be a promising approach in case of regeneration. In this investigation, electrospun polyurethanegraphene oxide scaffold was coated with polydopamine (PDA) by immersing the constructs in dopamine hydrochloride solution under the alkaline condition for 24 h. The present study aimed to investigate the synergic effects of graphene oxide (GO) and PDA on the osteogenic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…where V p is the volume of the scaffold pores; V S is the volume of the matrix; ρ s is the density; and ε is the porosity. 28…”
Section: Methodsmentioning
confidence: 99%
“…where V p is the volume of the scaffold pores; V S is the volume of the matrix; ρ s is the density; and ε is the porosity. 28…”
Section: Methodsmentioning
confidence: 99%
“…Several in vitro studies have demonstrated that PDA and DOPA coatings are effective in promoting stem cells and osteoblasts adhesion and growth on different fibrous scaffolds [ 125 , 126 , 127 , 128 , 129 ]. For example, a recent study has investigated the behavior of osteoblast-like cells exposed to a PDA-coated polyurethane (PU)-GO electrospun scaffold [ 130 ]. PDA deposition did not affect the structure of the PU-GO scaffold but significantly improved its hydrophilicity.…”
Section: Melanins and Melanin-like Materials In Tissue Engineeringmentioning
confidence: 99%
“…( d ) alkaline phosphatase (ALP) activity of MG-63 cultured in the presence or absence of PDA, for 1, 3, and 7 days (* p < 0.05, ** p < 0.005, *** p < 0.0005, **** p < 0.00005). Reproduced with permission from [ 130 ]. Copyright John Wiley and Sons, 2019.…”
Section: Figurementioning
confidence: 99%
“…Each material has a particular feature which will contribute to the overall efficacy of the scaffold. Conventionally, polymeric (synthetic and natural) and non‐polymeric materials are used for the fabrication of nanofiber scaffolds …”
Section: Introductionmentioning
confidence: 99%